ANALISIS ROI DAN EVA TERHADAP RETURN ON SHARES LQ-45 DI BURSA EFEK JAKARTA - NILAWATI NILAWATI (Jurnal Bisnis dan Akuntansi, 2004)
EVA as a performance evaluation system is used in many company today. UVA is different from to other companies performance evaluation system such as Return on Equity (ROE), Return on Investment (ROI), Residual Income and other performance indicator. EVA is a measurement system, which uses cost calculation, and make it different from to other significant performance measurement. This research is conducted find out whether there is relationship between ROI, EVA to Return on Shares at LQ45 company within 1997-2002. The result of research indicated that there is no relationship between ROI, EVA to Return on Shares.